Aktivitas Olahraga dengan Kejadian Sindrom Premenstruasi pada Anggota Perempuan UKM INKAI UNS - Arantika Meidya Pratiwi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
The purpose of this study is to determine the relationship between sport activies with premenstrual syndrome. Observational research methods using analytic techniques with cross sectional approach. This research was conducted at UKM (Unit of Student Activity) INKAI (Institute Karate Indonesia) UNS, on June 2012. The 36 sample of population from 40 of woman member was taken by simple random sampling. Analysis test with alpha= 0,05 obtained of Spearman rank correlation value at -0,821 that indicated strengthen correlation in negative direction. The signiﬁ cance value are 0,000 smaller than 0,05 that indicated Ho was rejected and Ha was accepted. The conclusion are any negative relationship between sports activities with the premenstrual syndrome, if the value of sports activity was higher the value of premenstrual syndrome was lower.